2021
DOI: 10.3390/ijms22042219
|View full text |Cite
|
Sign up to set email alerts
|

Runx3 Induces a Cell Shape Change and Suppresses Migration and Metastasis of Melanoma Cells by Altering a Transcriptional Profile

Abstract: Runt-related transcription factor-3 (Runx3) is a tumor suppressor, and its contribution to melanoma progression remains unclear. We previously demonstrated that Runx3 re-expression in B16-F10 melanoma cells changed their shape and attenuated their migration. In this study, we found that Runx3 re-expression in B16-F10 cells also suppressed their pulmonary metastasis. We performed microarray analysis and uncovered an altered transcriptional profile underlying the cell shape change and the suppression of migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Contrary to other RUNX family members predominantly implicated in the enhancement of metastasis, RUNX3 manifests an opposing role. Research conducted by Wang et al corroborated RUNX3's tumor-suppressive role in melanoma, particularly in inhibiting cell migration and metastasis [ 169 ]. In renal cell carcinoma, Zheng et al demonstrated that the downregulation of both RUNX3 and TGF-β in metastatic tissues, attributed to hypermethylation of CpG islands, is significantly associated with metastatic propensity and can be reversed by the application of a methylation inhibitor [ 85 ].…”
Section: Runx Family and The Intricate Landscape Of Tumor Metastasismentioning
confidence: 99%
“…Contrary to other RUNX family members predominantly implicated in the enhancement of metastasis, RUNX3 manifests an opposing role. Research conducted by Wang et al corroborated RUNX3's tumor-suppressive role in melanoma, particularly in inhibiting cell migration and metastasis [ 169 ]. In renal cell carcinoma, Zheng et al demonstrated that the downregulation of both RUNX3 and TGF-β in metastatic tissues, attributed to hypermethylation of CpG islands, is significantly associated with metastatic propensity and can be reversed by the application of a methylation inhibitor [ 85 ].…”
Section: Runx Family and The Intricate Landscape Of Tumor Metastasismentioning
confidence: 99%